IMPLEMENTASI PERIZINAN USAHA SARANG BURUNG WALET DI KELURAHAN TANJUNG KAPAL KECAMATAN RUPAT KABUPATEN BENGKALIS BERDASARKAN PERATURAN DAERAH KABUPATEN BENGKALIS NOMOR 7 TAHUN 2006 TENTANG PENGELOLAAN DAN PENGUSAHAAN SARANG BURUNG WALET - Angryani Br. Hombing; Dessy Artina; Adi Tiara Putri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2022)
This study discusses the implementation of swallow nest business licensing inTanjung Kapal Village, Rupat District, Bengkalis Regency in the perspective ofBengkalis Regency Regulation Number 7 of 2006 concerning Swallow's NestManagement and Concession. Article 8 paragraph 1 states that every person or entitythat will or has carried out a business in managing and operating a swallow's nest orexpanding its business must obtain a permit from the Regional Head in accordance withthe established procedure. The researcher took it t Rupat, Tanjung Kapal, becausethere are so many swallow nest businesses that do not make permits and even buildtheir buildings at a distance that is not in accordance with Regional Regulations andthe number of swallow nest business buildings increases every year. However, afterbeing ratified, the Regional Regulation has not been implemented properly.Sociological legal research uses primary data and secondary data, while the populationand sample are parties related to the problem studied by the authors carefullysupervised by the Bengkalis Regency Environmental Service, Horticultural Food Cropsand Livestock Service Office of Bengkalis Regency, and Regional Revenue TechnicalImplementation Unit (UPT).From the results of this study, the authors conclude that the role of the RegionalGovernment and related agencies above in carrying out supervision is carried out bythe Horticultural Food Crops and Livestock Service Office of Bengkalis Regency andthe Bengkalis Regency Environmental Service.Barriers to the implementation of management and exploitation of swallow's nestsrelated to permits are due to the lack of supervision and socialization of theintroduction of the Bengkalis Regency Regional Regulation No. 7 of 2006 Regarding th emanagement and exploitation of swallow's nests, no entrepreneur has come to apply fora swallow's nest permit and supervision does not work. because there are no complaintsfrom the community in Tanjung Kapal Village, Rupat District, Bengkalis Regencyagainst swallow nest entrepreneurs.Keywords: Licensing-Management and Concession of Swallow's Nest